Experimentul online, cunoaștere și autocunoaștere în învățământul teatral - Olăreanu, Cristinela (Theatrical Research, 2023)
The Online Experiment, Knowledge and Self-Knowledge in Theater Education The conveyance of emotions through the screen is more constrained than in a face-to-face interaction. Theatre, as an art form, relies on the direct interaction between the audience and actors. Although communication through the screen may limit the ability to convey emotions, modern technology can provide a range of tools to overcome these limitations and facilitate the transmission of emotions and experiences in an advantageous manner. In some situations, these constraints can be viewed as obstacles to be overcome in order to foster creativity, while in others, they may be perceived as impediments inhibiting the development of creativity. Encouraging the discovery and reinforcement of motivation aids in navigating challenging situations that arise in social contexts and contributes to strengthening one’s resilient personality. In difficult life situations, when individuals are subjected to constraints, vulnerability emerges. The actor examines their own vulnerabilities in order to tap into the human experience, thereby enhancing their capacity to comprehend the authentic emotional essence they possess. This understanding enables them to approach the emotions, behavior, actions, and thoughts of their character without dismissing or deeming it a weakness, as it serves as a tool to connect with their play character on the stage.